Stakeholder Discourse on Synthetic Fuels: A Positioning and Narrative Analysis - Dirk Scheer; Lisa Schmieder (Fuels, 2023)
The transition of mobility (in German “Verkehrswende”) as a fundamental part of the overall energy transition is a controversial field among stakeholders—in particular when it comes to synthetic fuels. There are considerable opposing views on the pros and cons of synthetic fuels within stakeholder communication. Against this background, the aim of this study was to research stakeholder positions and communication by identifying, systemizing, and assessing the bandwidth of stakeholder statements and views in Germany using a document-based positioning analysis. The objective was to provide the broadest possible range of (controversial) assessments on synthetic fuels’ future pathways. Based on a document analysis of 41 sources published by 17 stakeholders from the areas of economy, environment, and civil society in the last ten years, we analyzed commonalities and differences in the assessments of the synthetic fuels’ path as well as the reasons behind it. The results were synthesized in three narrative frames dominating the German discourse on synthetic fuels, namely: (1) synthetic fuels as a key component for the mobility transition; (2) synthetic fuels as an essential strategic niche management component, and (3) mobility transition as sustainable, affordable, safe, and comfortable mobility—with or without synthetic fuels.